Anisotropic Slippery Surfaces: Electric‐Driven Smart Control of a Drop's Slide. Issue 32 (19th May 2016) - Guo, Tianqi; Che, Pengda; Heng, Liping; Fan, Lizhen; Jiang, Lei
Abstract : Anisotropic slippery surfaces composed of directional, porous, conductive poly(3‐hexylthiophene) (P3HT) fibers, and silicone oil exhibit excellent anisotropic sliding properties for several liquid droplets and the reversible control of conductive liquid droplets sliding on these surfaces under the application of voltage.